Laser-Assisted Osteotomy for Implant Site Preparation: A Literature Review. Issue 1 (February 2017) - Moslemi, Neda; Shahnaz, Aysan; Masoumi, Samane; Torabi, Sepehr; Akbari, Solmaz
Abstract : Purpose: The aim of this study was to review the scientific evidence about the laser osteotomy in implant bed preparation. Methods: An electronic search was performed on relevant English articles up to April 2016 in the PubMed, Scopus, and Google Scholar databases. Results: Twenty-two articles (1 clinical, 13 animal, and 8 ex vivo studies) were included. Implant sites prepared by erbium family lasers and drill showed comparable results regarding the percentage of bone-to-implant contact, values of biomechanical tests, and healing process. Selection of proper laser wavelength and parameters was of paramount importance to minimize the risk of thermal bone damage. Lack of depth control and long time needed for implant site osteotomy with laser were the most challenging concerns for its clinical applicability. Computer-guided laser osteotomy showed promise for future use of laser osteotomy in clinical settings. Conclusion: Evidence from animal studies shows promising results regarding laser osteotomy in implant site preparation. However, because of the lack of clinical studies, it is not possible to make a conclusive result whether there is superiority of laser osteotomy in clinical practice.